Automatização no diagnóstico de nível de língua: anotação e versatilidade dos recursos para PLE - Amaro, Raquel; Correia, Susana; Gramacho, Carolina; Mendes, Amália (Revista da Associação Portuguesa de Linguística, 2020)
The automatic diagnosis and analysis of the production of foreign language learners can contribute to overcome linguistic barriers that hinder the integration of migrant populations. The richness and complexity of the phenomena observed in this context and the multiplicity of objectives served by automatic analysis tools demonstrate the inevitability of manual annotation of data and the importance of producing versatile resources, in order to maximize their usability. The present study aims, therefore, to contrast the needs of automatic diagnosis systems and the analysis of the phenomena reflected in the annotations for European Portuguese, based on COPLE2 and the corpora analysis conducted within the scope of the POR Nível project, proposing a system of annotation that includes error annotation and annotation of structures associated with complexity. The results highlight the need to enhance the usability of resources, to acknowledge their value and to promote the necessary investment in their development.